STRATEGI PENERAPAN PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN IPAS KELAS V DI SDN PANGARANGAN VII - Rindiyani, Nuva; Sari, Tita Tanjung; Andiriyanto, Ach. (Universitas Tanjungpura, 2025)
Differentiated learning is an effort made by teachers to adjust the learning process in the classroom to meet students' learning needs. Differentiated learning is important to do because it can create inclusivity, involvement and improve student learning outcomes. However, not all schools implement differentiated learning due to the low understanding of teachers regarding differentiated learning. Therefore, this study aims to describe the strategy for implementing differentiated learning in the subject of social studies for grade V at SDN Pangarangan VII and to describe the challenges faced by teachers in implementing differentiated learning in the subject of social studies for grade V at SDN Pangarangan VII. This study uses a qualitative approach with a case study type. The results of this study indicate that the teacher's strategy in implementing differentiated learning in the subject of social studies at SDN Pangarangan VII is to use several stages, namely the planning stage, the implementation stage and the evaluation stage. The differentiated learning carried out is the differentiation of content, process, product and learning environment. In implementing this learning, teachers experience several challenges, including students who are still passive, concerns about misunderstandings with parents or guardians of students and the many preparations that need to be made in implementing differentiated learning, but teachers have made efforts to overcome these challenges.